Uma abordagem MDE para Modelagem e Verificação de Documentos Multimídia Interativos - Picinin Júnior, Delcino; Farines, Jean-Marie; Santos, Celso A. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
This paper proposes an Model-Driven Engineering approach for modeling and verificating of interactive multimedia applications. The approach introduces a toolchain based on FIACRE language, that is used both as the target language of model transformation engines from NCL multimedia model, and as the source language of compilers into the targeted verification toolbox Tina. The paper illustrates the proposed approach with a case study of a NCL-based interactive TV application.